Kontribusi Motivasi Belajar, Persepsi Siswa Terhadap Kemampuan Mengajar Guru, dan Pemanfaatan Fasilitas Sekolah Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP Al-Islam Kartasura Tahun Ajaran 2015/2016 - Apriyanto, Gangsar, Drs. Slamet H.W., M.Pd (2016)
Gangsar Apriyanto / A410120118. CONTRIBUTION LEARNING MOTIVATION, STUDENT PERCEPTION OF TEACHING ABILITY TEACHERS, AND USE OF SCHOOL FACILITIES OF LEARNING MATH CLASS VIII SMP AL - ISLAM Kartasura 2015/2016. Essay. Faculty of Teacher Training and Education. Muhammadiyah University of Surakarta. In June, 2016. The purpose of this research to analyze and examine: (1) the contribution of learning motivation to the learning outcomes of mathematics, (2) the contribution of students' perceptions about the teaching capabilities of the learning outcomes of mathematics, (3) the contribution of the use of school facilities for learning outcomes mathematics, (4) contributions learning motivation, students' perceptions about the ability of teachers to teach, and the use of school facilities for learning outcomes in mathematics. This type of research is quantitative. The study population was taken from across graders VIII SMP Al-Islam Kartasura number of 117 students. The research sample consisted of 60 students selected at random. Retrieval of data from questionnaires and documentation. Data were analyzed using multiple linear regression, t test, and test F. The results: (1) there is a contribution to the learning outcomes motivation to learn mathematics, the relative contribution of 99.1%, (2) there is no contribution of students' perceptions about the ability of teachers to teach to the mathematics learning outcomes, the relative contribution of 0.78% (3) there is no contribution of the use of school facilities for learning outcomes mathematics, the relative contribution of just 0.012% (4) there is a contribution of learning motivation, students' perceptions about the ability of teachers to teach, and the utilization of school facilities to mathematics learning outcomes, the coefficient of determination of 18.9%. Keywords: learning motivation, learning outcomes, school facilities, student achievment, teaching capabilities.